An improved control strategy using TCSC with grey wolf-optimized DSTATCOM for efficient LVRT of DFIG-based WECS. (November 2022) - Kumar, Ashwani; Mishra, Vishnu Mohan; Ranjan, Rakesh
Doubly fed induction generator (DFIG)-based wind energy conversion systems (WECSs) are widely used for its advantage over other schemes, as it enables the connection to the grid even during faults and provides reactive power compensation. However, transient stability of DFIG and low voltage ride through (LVRT) remained an area of improvement. In this paper, a hybrid approach is proposed to improve the efficiency of the DFIG WECS using grey wolf-optimized distribution static compensator (DSTATCOM) with thyristor-controlled series capacitor (TCSC). Extensive simulation analysis was performed considering design parameters as an objective function. The optimal values of proportional–integral (PI) coefficients were found to minimize the objective function. Using MATLAB, time-domain simulations were carried to confirm the efficiency of the optimized control system. Simulation results further confirm that the combination of TCSC and DSTATCOM may be considered as a promising scheme to enhance fault ride through (FRT) capability of WECS during the normal and unstable conditions.